Analysis of old master paintings by direct temperature-resolved time-of-flight mass spectrometry: Some recent developments - van Loon, Annelies; Genuit, Wim; Pottasch, Carol; Smelt, Susan; Noble, Petria (Microchemical journal, 2016)
Direct temperature-resolved mass spectrometry (DTMS) is an analytical technique in which small (μg) amounts of sample are applied to a filament and introduced into the ion source of a mass spectrometer. It is a fast fingerprinting method particularly suitable for the characterization of oils, resins, waxes, and other compound classes in tiny complex samples from paintings. DTMS results reported thus far have been obtained using instruments with nominal mass resolution. Higher mass resolutions can be achieved by magnetic sector mass spectrometers only at the expense of a severe loss of sensitivity. Modern time-of-flight mass spectrometers, however, do provide both high resolution and high sensitivity simultaneously. The availability of accurate mass information adds another dimension to DTMS. The difference between the nominal and accurate mass, the mass defect, may be graphically presented in so-called ‘Kendrick plots’. These can be used as fingerprints, enabling a quick overview of the main features in high-resolution mass spectra of complex mixtures. This paper combines DTMS with Kendrick mass defect analysis applied to a series of reference compounds commonly found in paintings. Finally, we also present the results of analysis of samples taken from the 17th-century painting of Saul and David by Rembrandt van Rijn (Mauritshuis, The Hague) that has been recently subjected to extensive conservation treatment. •Advances in the application of DTMS for the analysis of microsamples of paintings.•Use of a modern time-of-flight mass spectrometer.•Providing high sensitivity and high mass resolution at the same time.•Kendrick mass defect analysis based on the accurate masses.•Results of analysis of conservation materials and Rembrandt's Saul and David.